Structural, surface and luminescence properties of Ca3B2O6:Dy3+ phosphors. Issue 5 (April 2016) - Manhas, M.; Kumar, Vinay; Ntwaeaborwa, O.M.; Swart, H.C.
Abstract: Dy 3+ doped Ca3 B2 O6 phosphors were synthesized by combustion method at 600 °C, using urea as fuel, and their surface, spectral, photoluminescence (PL) and thermoluminescence (TL) properties were investigated. The structural properties of the phosphor were examined by the powder X-ray diffraction method after annealing the phosphor at 900 °C for 3 h. PL and UV–vis spectroscopy were carried out to study the spectral properties of the Ca3 B2 O6 :Dy 3+ phosphors. X-ray photoelectron spectroscopy (XPS) was used to investigate the elemental compositions, electronic and chemical states of the synthesized phosphor. Under near UV excitation at 348 nm, the Ca3 B2 O6 :Dy 3+ phosphor emitted intense blue and yellow emission with a weak red band centered at 480 nm, 578 nm and 667 nm, respectively, resulting from the 4 F9/2 → 6 H x /2 ( x =15, 13 and 11) transitions of the Dy 3+ ion. The diffuse reflectance (DR) spectra were used to calculate the band gap of the material. The TL data were recorded after exposing the material to different gamma doses in the range of 1 kGy–5 kGy. TL spectra for Ca3 B2 O6 :Dy 3+ phosphor showed one broad peak centered at 384 K. The effects of Dy 3+ concentration and different heating rates on the TL glow curves were also investigated. The calculated CIE coordinates (0.38, 0.40) were found to be close to the white region of the horse shoe plot of color gamut.